Polyethylene composition and molded article

A tailored polyethylene composition with precise density and molecular characteristics addresses the issues of stiffness and adhesive residue in surface protection films, ensuring stable film formation and processing at high temperatures.

JP7661441B2Active Publication Date: 2025-04-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 22 Cites 0 Cited by

Patent Information

Application Number
JP2023178956
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-17
Filing Date
2023-10-17
Publication Date
2025-04-14
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

Existing polyethylene compositions used in surface protection films lack sufficient stiffness at high temperatures, leave adhesive residue, and have poor film-forming processability, particularly when exposed to high temperatures during processing.

Method used

A polyethylene composition with specific density, molecular weight, crystallinity, and crystallite size, along with controlled ratios of high-density and low-density polyethylenes, is formulated to enhance stiffness, reduce adhesive residue, and improve film-forming processability at high temperatures.

Benefits of technology

The composition exhibits excellent stiffness when formed into films at high temperatures, minimizes adhesive residue during high-temperature processing, and ensures stable film-forming processability, reducing film breakage and wrinkles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661441000001
    Figure 0007661441000001
  • Figure 0007661441000002
    Figure 0007661441000002
  • Figure 0007661441000003
    Figure 0007661441000003
Patent Text Reader

Abstract

To provide a polyethylene composition with excellent resilience during high temperature processing, minimal adhesive deposit during high temperature processing, and excellent film forming processability.SOLUTION: There is provided a polyethylene composition that satisfies the following conditions [A] to [D]: <condition (A)>The weight average molecular weight in gel permeation chromatography (GPC) measurement is 40,000 g / mol or more and 350,000 g / mol or less. <condition (B)>The degree of crystallinity calculated by wide-angle X-ray scattering (WAXS) measurement is 60% or more and 75% or less. <condition (C)>The crystallite size of the (110) plane calculated by the wide-angle X-ray scattering measurement is 17 nm or more and 32 nm or less. <condition (D)>The ratio Y / X of the peak intensity X derived from the (110) plane at 50°C to the peak intensity Y derived from the (110) plane at 130°C in the temperature variable wide-angle X-ray scattering measurement is 0.40 or more and 0.80 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyethylene composition and a molded article. [Background technology]

[0002] Polyethylene compositions are molded by various molding methods and used in a wide range of applications, and the properties required vary depending on the molding method and application. A representative application of the polyethylene composition is a film. Specifically, a surface protection film for optical components and the like is known. The surface protection film is applied to the surface of an adherend such as a metal plate, a resin plate, a wooden decorative plate, a nameplate, a liquid crystal component, an electric / electronic component, a building material, and an automobile component for the purpose of preventing the occurrence of scratches and stains from the outside during processing, transportation, and storage.

[0003] The surface protection film is required to have stiffness in order to prevent wrinkles and improve handling during peeling. In addition, the surface protection film is required to be thin and take up at high speed in order to reduce costs and environmental load. On the other hand, when the polyethylene composition constituting the surface protection film does not contain low-density polyethylene or when the content of the low-density polyethylene is extremely low, the film is prone to become unstable and shake immediately after leaving the die, which can lead to film breakage, uneven thickness, and poor appearance of the film.

[0004] On the other hand, in the production process of the adherend, the surface protection film may be heat-processed while attached to the adherend. Even if the surface protection film is exposed to high temperatures, it is preferable that the surface protection film does not melt or deform, realizing surface protection of the adherend, and that the polyethylene composition does not remain on the adherend when peeled off. However, when low-density polyethylene is blended into the polyethylene composition constituting the surface protection film, the melting point of the surface protection film is lowered, which causes a problem of deformation and adhesive residue during high-temperature processing of the adherend.

[0005] In consideration of the problems of film breakage, thickness deviation, and poor film appearance of the surface protection film described above, Patent Document 1 discloses a polyethylene composition that achieves both reduced FE (fish eyes) and sufficient stiffness at room temperature by adding a small amount of low-density polyethylene to a high-density polyethylene, thereby improving film breakage, thickness deviation, and film appearance. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6792957 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Document 1, no verification was carried out with respect to adhesive residue when the adherend is processed at high temperatures, or the film-forming processability of the film, and there is a problem in that there is room for improvement.

[0008] Accordingly, an object of the present invention is to provide a polyethylene composition which exhibits excellent stiffness when formed into a film at high temperatures, leaves little adhesive residue when an adherend is processed at high temperatures, and further exhibits excellent film-forming processability. [Means for solving the problem]

[0009] Means for Solving the Problems of the Prior Art The present inventors have conducted intensive research to solve the above-mentioned problems of the prior art and as a result have found that a polyethylene composition having the specific properties described below can solve the above-mentioned problems of the prior art, thereby completing the present invention. That is, the present invention is as follows.

[0010] [1] Density 942kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 Contains the following high-pressure low-density polyethylene (B):<Condition (A)>~<Condition (D)> below , and <Condition (F)> The polyethylene composition satisfies the above. <Condition (A)> The weight average molecular weight as measured by gel permeation chromatography (GPC) is 40,000 g / mol or more and 350,000 g / mol or less. <Condition (B)> The degree of crystallinity calculated by wide-angle X-ray scattering (WAXS) measurement is 60% or more and 75% or less. <Condition (C)> The crystallite size of the (110) plane calculated by the wide-angle X-ray scattering measurement is 17 nm or more and 32 nm or less. <Condition (D)> In a variable temperature wide-angle X-ray scattering measurement, the ratio Y / X of the peak intensity X derived from the (110) plane at 50°C to the peak intensity Y derived from the (110) plane at 130°C is 0.40 or more and 0.80 or less. <Condition (F)> Cross fractionation chromatography (CFC) temperature rising elution fractionation (TREF) up to 80°C The mass ratio of the eluted components is 1% by mass or more and 35% by mass or less of the total eluted amount. [2] The polyethylene composition according to [1] above, wherein, in a three-component approximation of a free induction decay curve obtained by the Carr Purcell Meiboom Gill (CPMG) method in pulse NMR measurement at 180°C, the relaxation time Tα of a low mobility component α is 5 ms or more and 25 ms or less, and the abundance ratio Rα of the low mobility component α is 25% or more and 55% or less. 〔3〕 The polyethylene composition comprises: Density 942kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 below High Pressure Method A mixture of low density polyethylene (B), The above High Pressure MethodThe low-density polyethylene (B) has a low-mobility component ratio calculated by the following formula I, which is calculated from the abundance ratio Rα of the low-mobility component α and the abundance ratio Rβ of the intermediate component β when a free induction decay curve obtained by a Carr Purcell Meiboom Gill (CPMG) method in a pulse NMR measurement at 180°C is approximated as a three-component curve, and is 0.35 or more and 0.55 or less. Or [2] The polyethylene composition according to claim 1. (Ratio of low mobility components) = Rα / (Rα+Rβ) (Equation I) 〔4〕 The polyethylene composition comprises: Density 942kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 below High Pressure Method A mixture of low density polyethylene (B), The high-density polyethylene (A) has a low-mobility component ratio calculated by the following (formula I) from the abundance ratio Rα of the low-mobility component α and the abundance ratio Rβ of the intermediate component β when a free induction decay curve obtained by a Carr Purcell Meiboom Gill (CPMG) method in pulse NMR measurement at 180°C is approximated as three components, and the low-mobility component ratio is 0.50 or more and 0.70 or less. Or [2] The polyethylene composition according to claim 1. (Ratio of low mobility components) = Rα / (Rα+Rβ) (Equation I) 〔5〕 The content of the high-density polyethylene (A) is 70% by mass or more and 99% by mass or less, The above High Pressure Method The content of the low-density polyethylene (B) is 1% by mass or more and 30% by mass or less. [3] or [4] The polyethylene composition according to claim 1. 〔6〕 The above [1] to 〔5〕 2. A molded article comprising the polyethylene composition according to claim 1. 〔7〕 The film is 〔6〕 The molded article according to claim 1. Effect of the Invention

[0011] INDUSTRIAL APPLICABILITY The present invention can provide a polyethylene composition which exhibits excellent stiffness when formed into a film at high temperatures, leaves little adhesive residue when an adherend is processed at high temperatures, and has excellent film-forming processability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the following embodiment is merely an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be implemented in various modifications within the scope of the gist thereof.

[0013] [Polyethylene composition] The polyethylene composition of the present embodiment satisfies the following <Condition (A)> to <Condition (D)>. <Condition (A)> The weight average molecular weight as measured by gel permeation chromatography (hereinafter sometimes referred to as GPC) is 40,000 g / mol or more and 350,000 g / mol or less. <Condition (B)> The degree of crystallinity calculated by wide-angle X-ray scattering (hereinafter sometimes referred to as WAXS) measurement is 60% or more and 75% or less. <Condition (C)> The crystallite size of the (110) plane calculated by the WAXS measurement is 17 nm or more and 32 nm or less. <Condition (D)> In a variable-temperature WAXS measurement, the ratio Y / X of the peak intensity X derived from the (110) plane at 50°C to the peak intensity Y derived from the (110) plane at 130°C is 0.40 or more and 0.80 or less.

[0014] By having a constitution that satisfies the above conditions (A) to (D), it is possible to obtain a polyethylene composition that has excellent stiffness when the film is processed at high temperatures, leaves little adhesive residue when the adherend is processed at high temperatures, and further has excellent film-forming processability.

[0015] It is preferable that the polyethylene composition of the present embodiment further satisfies at least any one of the following <Condition (E)> to <Condition (H)>. This makes it possible to obtain a polyethylene composition that has excellent stiffness during high-temperature processing of a film, leaves little adhesive residue during high-temperature processing of an adherend, and has excellent film-forming processability.

[0016] <Condition (E)> In pulsed NMR measurements at 180°C, the free induction decay curve obtained by the Carr Purcell Meiboom Gill (hereinafter sometimes referred to as CPMG) method is approximated with three components, and the relaxation time T α is 5 ms or more and 25 ms or less, and the presence ratio R of the low-motion component α α is between 25% and 55%.

[0017] <Condition (F)> The mass ratio of components eluted at temperatures up to 80°C in temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC) is 1% by mass or more and 35% by mass or less of the total elution amount.

[0018] <Condition (G)> The polyethylene composition of the present embodiment has a density of 942 kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 The low-density polyethylene (B) is a mixture of the following low-density polyethylenes, and when the low-density polyethylene (B) is measured by pulse NMR at 180° C., when a free induction decay curve obtained by the CPMG method is approximated as three components, the presence ratio R of the low-mobility component α is α and the abundance ratio R of intermediate component β β The low mobility component ratio calculated by the following formula (I) is 0.35 or more and 0.55 or less. (Low Motility Component Ratio) = R α / (R α +R β ) (Formula I)

[0019] <Conditions (H)> The polyethylene composition of the present embodiment has a density of 942 kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 The mixture of the following low-density polyethylene (B), wherein the high-density polyethylene (A) is a mixture of the following low-density polyethylene (B) and the following low-density polyethylene (B) in which, when a free induction decay curve obtained by a CPMG method is approximated by three components in a pulse NMR measurement at 180°C, the presence ratio R α and the abundance ratio R of intermediate component β β The low mobility component ratio calculated by the above formula (I) is 0.50 or more and 0.70 or less. (Low Motility Component Ratio) = R α / (R α +R β ) (Formula I)

[0020] The polyethylene composition of the present embodiment has a density of 942 kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 It is preferable that the composition contains the following low-density polyethylene (B). The low-density polyethylene (B) may be a high-pressure low-density polyethylene, a linear low-density polyethylene, or another special ultra-low-density polyethylene. Among these, the high-pressure low-density polyethylene is preferred from the viewpoint of improving stability during film processing. Such polyethylene compositions tend to have both heat resistance and film processing stability.

[0021] The polyethylene contained in the polyethylene composition of the present embodiment may be a homopolymer of ethylene, or a copolymer of ethylene with an α-olefin, a cyclic olefin, a diene, or a derivative thereof, or may contain two or more types of (co)polymers.

[0022] The polyethylene composition of the present embodiment is not particularly limited, and can be produced, for example, by melt-kneading a high-density polyethylene (A) and a low-density polyethylene (B). The production method of the polyethylene composition of the present embodiment will be described in detail below. The high density polyethylene (A) has a density of 942 kg / m 3 Low density polyethylene (B) is polyethylene having a density of 930 kg / m or more. 3 The following is the result. The method for producing the raw material polyethylene is not particularly limited, and any of the commonly used production methods such as the solution method, high pressure method, high pressure bulk method, gas method, and slurry method can be used.

[0023] (Weight average molecular weight) As indicated in the above <Condition (A)>, the polyethylene composition of the present embodiment has a weight average molecular weight measured by GPC of 40,000 g / mol or more and 350,000 g / mol or less. The lower limit is preferably 60,000 g / mol or more, more preferably 80,000 g / mol or more, and the upper limit is preferably 300,000 g / mol or less, more preferably 250,000 g / mol or less. A weight average molecular weight of 40,000 g / mol or more is preferable because it can reduce neck-in during film formation and also has a high viscosity during extrusion, making it easy to disperse fish eyes (FE). A weight average molecular weight of 350,000 g / mol or less is preferable because it can suppress film tearing and improve adhesion to an adherend. The weight average molecular weight of the polyethylene composition can be measured by the method described in the Examples below.

[0024] The weight average molecular weight of the polyethylene composition can be controlled within the above-mentioned numerical range by adjusting the polymerization conditions, selecting the types of raw materials, and adjusting the mixing ratio of the raw materials. As a method for controlling the molecular weight, for example, in the slurry method, the molecular weight tends to increase by using a highly active polymerization catalyst or by reducing the concentration of hydrogen, which is a molecular weight regulator, while in the high pressure method, the molecular weight tends to increase by lowering the polymerization temperature, increasing the polymerization pressure, or not using a chain transfer agent.

[0025] (Crystallization degree) As shown in the above <Condition (B)>, the polyethylene composition of the present embodiment has a crystallinity calculated by wide-angle X-ray scattering (WAXS) measurement of 60% or more and 75% or less, preferably 62% or more, and more preferably 64% or more. Also, it is preferably 73% or less, and more preferably 71% or less. The polyethylene composition of the present embodiment preferably has a crystallinity of 60% or more, since sufficient stiffness can be obtained when processed into a film, and stiffness during high-temperature processing tends to be good. Also, a crystallinity of 75% or less is preferable, since neck-in of the film tends to be small, high-speed processability tends to be good, and FE can be reduced by the branched components. The crystallinity of the polyethylene composition of the present embodiment can be measured by the method described in the Examples below.

[0026] The crystallinity calculated by wide-angle X-ray scattering (WAXS) measurement of the polyethylene composition can be controlled to be within the above-mentioned numerical range by adjusting the polymerization method, composition, and mixing method of the components contained in the polyethylene composition. Examples of methods for controlling the crystallinity of the polyethylene composition include, for example, a slurry method in which a comonomer, i.e., a monomer other than ethylene, is mixed into the ethylene raw material, which tends to reduce the crystallinity of the polyethylene composition. Also, a high-pressure method includes a method in which a chain transfer agent is not used, which makes it difficult to terminate radical polymerization and makes long-chain branching reactions more likely to occur, which tends to reduce the crystallinity of the polyethylene composition. The crystal structure of polyethylene is influenced by the molecular structure and degree of entanglement of the components contained in the polyethylene composition. For example, polyethylene having a branched structure or polyethylene having an entangled structure is easily inhibited from crystallizing, so that polyethylene compositions containing these tend to have a low degree of crystallinity. On the other hand, linear polyethylene and polyethylene with little entanglement are easily crystallized, so that polyethylene compositions containing these tend to have a high degree of crystallinity. In addition, when the polyethylene composition of the present embodiment is a mixture of polyethylenes, the degree of crystallinity changes depending on the type and composition ratio of the polyethylene raw materials constituting the composition, and it is considered that the secondary structure changes due to the interaction of the difference in molecular structure, compatibility, and entanglement.

[0027] (Crystallite size) As shown in the above <Condition (C)>, the polyethylene composition of the present embodiment has a (110) crystallite size calculated by wide-angle X-ray scattering (WAXS) measurement of 17 nm or more and 32 nm or less, preferably 19 nm or more, and more preferably 21 nm or more. The crystallite size is preferably 30 nm or less, and more preferably 28 nm or less. The crystallite size of the (110) plane represents the crystal thickness in the direction perpendicular to the molecular chain. A polyethylene composition having a small crystallite size tends to have low molecular weight components easily eluted during high-temperature processing of the polyethylene composition, while a polyethylene composition having a large crystallite size is excellent in heat resistance and low elution property, but tends to have a short stress relaxation time and large neck-in during film formation. It is preferable that the crystallite size of the (110) plane is 17 nm or more, since adhesive residue during high-temperature processing of the adherend is reduced.It is also preferable that the crystallite size of the (110) plane is 32 nm or less, since neck-in during film formation is reduced, yield is improved, and wrinkles are less likely to occur in the film. The crystallite size of the polyethylene composition of the present embodiment can be measured by the method described in the Examples below.

[0028] The crystallite size of the (110) plane of a polyethylene composition is affected by the composition of the polyethylene composition and the molecular structure of the components contained therein. For example, when the polyethylene composition contains a polyethylene having a branched structure or an entangled structure, the crystallite size of the (110) plane tends to be small. On the other hand, when the polyethylene composition contains a linear polyethylene or a polyethylene with little entanglement, the crystallite size of the (110) plane tends to be large. The branched structure and entangled structure of the components contained in the polyethylene composition can be adjusted by changing the catalyst preparation method or polymerization conditions, and thus the crystallite size of the (110) plane of the polyethylene composition can be controlled within the above-mentioned numerical range. Specifically, when preparing a polymerization catalyst used in the slurry method, by adjusting the number of times of supporting the active species to increase the supporting concentration, the polyethylene growth points on the catalyst surface are dense, and since there are multiple active species, entanglement during the polyethylene growth process is promoted, and a polyethylene with a large number of entangled structures tends to be obtained. More specifically, in order to obtain a polyethylene with a large number of entangled structures, it is preferable to support titanium, which is a catalyst species, in the process of synthesizing a Ziegler-Natta catalyst, two times and set the molar ratio of the active species added in each supporting operation to 1:3 (first supporting operation: second supporting operation). On the other hand, a polyethylene composition polymerized using a catalyst with a low supporting density of the active species or a polyethylene composition polymerized with a metallocene catalyst with one type of active species tends not to promote entanglement, and a polyethylene with a linear structure or a small number of entangled structures is obtained.

[0029] Furthermore, examples of methods for obtaining polyethylene having a highly entangled structure include a method of mixing a low-density polyethylene produced without adding a chain transfer agent into a polyethylene composition, and a method of mixing a high-pressure low-density polyethylene produced by increasing the separation temperature and appropriately controlling the residence time in a gas separation apparatus for unreacted ethylene gas in a production process for high-pressure low-density polyethylene into a polyethylene composition. By increasing the temperature of the gas separation device for unreacted ethylene gas and immediately separating the unreacted ethylene gas, the unreacted radicals remaining in the system are more likely to cause a bonding reaction between polyethylenes, and by controlling the residence time, decomposition of polyethylene does not occur. As a result, low-density polyethylenes having a long-chain branched structure tend to bond with each other to produce low-density polyethylene having a branched structure that spreads like a tree. Specifically, by setting the temperature of the gas separation device immediately after the reactor to 220°C or higher and setting the residence time to 15 minutes or less, high-pressure low-density polyethylene having a long-chain branched structure with a high molecular weight tends to be produced. By including such low-density polyethylene having a long-chain branched structure, an entanglement structure is increased, and polyethylene with a small crystallite size is obtained.

[0030] Furthermore, when the polyethylene composition of the present embodiment is a mixture of polyethylenes, the crystallite size of the (110) plane of the polyethylene composition changes depending on the types and compositional ratio of the constituent polyethylene raw materials. This is considered to be because the secondary structure changes due to differences in molecular structure, compatibility, and entanglement. The WAXS measurement applied to measure the crystallite size of the (110) plane of the polyethylene composition of the present embodiment can be carried out using a general wide-angle X-ray scattering measurement device, and can be carried out, for example, by the method described in the examples described below.

[0031] (Variable temperature WAXS measurements) As shown in the above <Condition (D)>, in the polyethylene composition of the present embodiment, the ratio Y / X of the peak intensity X derived from the (110) plane at 50°C to the peak intensity Y derived from the (110) plane at 130°C, as measured by variable temperature wide-angle X-ray scattering (WAXS), is 0.40 or more and 0.80 or less, preferably 0.45 or more, more preferably 0.50 or more, and preferably 0.75 or less, more preferably 0.70 or less. Y / X is an index showing the extent to which the crystal structure of polyethylene is maintained at 130° C. When Y / X is 0.40 or more, the peak intensity derived from the (110) plane is sufficiently maintained even at 130° C., and a surface protection film using the polyethylene composition of the present embodiment has sufficient strength when subjected to high-temperature treatment and leaves less adhesive residue on an adherend, which is preferable. Furthermore, when Y / X is 0.80 or less, the polyethylene composition of the present embodiment contains a certain amount of low-density components, and therefore the film-forming processability of the polyethylene composition of the present embodiment is improved, which is preferable.

[0032] The variable-temperature WAXS measurement method applied to the measurement of the polyethylene composition of the present embodiment is not particularly limited as long as the WAXS measurement is performed with a sample set on a heating stage, and can be carried out, for example, by the method described in the examples described below.

[0033] Y / X can be controlled to fall within the above-mentioned range by adjusting the polymerization method, composition, and mixing method of the components contained in the polyethylene composition. The method is not particularly limited, but for example, when the polyethylene composition contains a density of 950 kg / m 3 By including the above components (hereinafter sometimes referred to as high-density components) in an amount of 75 mass % or more, it is possible to control Y / X to 0.40 or more. For example, the polyethylene composition may contain a density of 925 kg / m 3 By including 1 mass % or more of the following component (hereinafter, sometimes referred to as a low-density component), Y / X can be controlled to 0.80 or less.

[0034] The method for containing a low-density component in the polyethylene composition is not particularly limited, but examples thereof include a method of mixing a low-density polyethylene into a high-density polyethylene and a method of incorporating a low-density polyethylene into a high-density polyethylene by a multi-stage polymerization process.

[0035] On the other hand, in a polyethylene composition containing a high density component and a low density component, the melting point of the high density component tends to be lower than the melting point of the same high density component alone. The reason for this is that when a polyethylene composition containing a high density component and a low density component in a solid state is heated, the low density component melts first. It is considered that the melted low density component promotes the crystalline melting of the high density component, so that the melting point of the high density component in the polyethylene composition tends to decrease. For this reason, in a polyethylene composition simply containing a high density component and a low density component, the low density component with a low melting point melts first during the temperature rise process of the variable temperature WAXS measurement, and the melted low density component promotes the crystalline melting of the high density component, so that the peak intensity Y derived from the (110) plane at 130 ° C. tends to decrease significantly. Therefore, by suppressing the promotion of crystalline melting of the high density component by the melted low density component and preventing the decrease in the peak intensity Y derived from the (110) plane at 130 ° C., the Y / X can be made 0.40 or more.

[0036] In order to control the Y / X ratio within the numerical range of 0.40 or more and 0.80 or less, it is effective to precisely control the molecular mobility of the polyethylene composition and the entanglement structure between the molecules. A polyethylene composition having strong entanglement between its molecules tends not to have a decrease in the peak intensity Y derived from the (110) plane even at 130°C. This is believed to be because a part of the molecular chain of the low-density component is easily incorporated into the crystal structure formed by the high-density component, and the crystal structure tends to be maintained even at 130°C. The strength of entanglement between the molecules of the polyethylene composition can be evaluated by pulse NMR, which will be described later.

[0037] Methods for strengthening the entanglement of molecules in the polyethylene composition include, for example, adjusting the preparation method of the polymerization catalyst or the polymerization conditions, thereby controlling the molecular growth of polyethylene. For example, when preparing a polymerization catalyst used in the slurry method, the loading concentration is increased by adjusting the number of loadings of active species, thereby concentrating the polyethylene growth points on the catalyst surface and providing multiple active species. This tends to promote the entanglement of molecules during the polyethylene growth process, resulting in a polyethylene composition with strong entanglement. Specifically, in the process of synthesizing a Ziegler-Natta catalyst, when supporting titanium, which is a catalyst species, it is preferable to load the catalyst twice and set the molar ratio of the active species added in each loading operation to 1:3 (first loading operation: second loading operation). On the other hand, in a polyethylene composition polymerized using a catalyst having a low supporting density of the active species, or in a polyethylene composition polymerized using a metallocene catalyst having one type of active species, entanglement tends not to be promoted easily, and a polyethylene having a less entangled structure tends to be obtained.

[0038] Moreover, as a method for strengthening the entanglement of molecules in the polyethylene composition, for example, a method of containing a component that easily forms physical crosslinking points can be mentioned. Such a polyethylene composition containing a component that easily forms physical crosslinking points is likely to crystallize in a state in which the molecular chains are entangled in the cooling step in the molding process, and therefore tends to easily maintain a crystalline structure even at 130°C. Furthermore, in such a polyethylene composition, the molecular chains of the low-density component that melts first in the temperature rise process are bound by entanglement, and therefore promotion of crystalline melting of the high-density component tends to be suppressed. Examples of the method for incorporating a component that easily forms physical crosslinking points into the polyethylene composition include a method for incorporating a low-density component having a long-chain branched structure spreading in a dendritic manner into the polyethylene composition. Examples of the method for incorporating such a low-density component include a method of mixing a high-pressure low-density polyethylene produced without adding a chain transfer agent into the polyethylene composition, and a method of producing high-pressure low-density polyethylene by increasing the separation temperature and appropriately controlling the residence time in a gas separator for unreacted ethylene gas in a production process for high-pressure low-density polyethylene, and mixing the high-pressure low-density polyethylene into the polyethylene composition. As described above, by increasing the separation temperature in the gas separation apparatus for unreacted ethylene gas and immediately separating the unreacted ethylene gas, the unreacted radicals remaining in the system are likely to cause a bonding reaction between polyethylene molecules, and by appropriately controlling the residence time, decomposition of polyethylene tends not to occur. As a result, low-density polyethylene molecules having a long-chain branched structure tend to bond to each other, and a low-density polyethylene having a branched structure spreading like a tree tends to be produced. Specifically, by setting the temperature of the gas separation apparatus immediately after the reactor to 220°C or higher and setting the residence time to 15 minutes or less, a high-pressure low-density polyethylene having a long-chain branched structure with a high molecular weight tends to be produced. This leads to stronger entanglement of the molecules of the polyethylene composition as described above.

[0039] In order to control Y / X within the above-mentioned numerical range, there can be mentioned a method of improving the dispersibility of the polyethylene composition in the extrusion step. By improving the dispersibility, various components in the polyethylene composition in a molten state become uniform, and by cooling in that state in a cooling step in various molding methods, the composition is crystallized in a state in which the molecular chains are entangled, and a decrease in the peak intensity Y derived from the (110) plane at 130°C is suppressed, so that the Y / X can be controlled within the above-mentioned numerical range. Methods for improving the dispersibility in the extrusion step of the polyethylene composition include, but are not limited to, a method in which the low-density component and the high-density component are previously pelletized, dry-blended, and then melt-kneaded, and a method in which the polyethylene composition containing the low-density component and the high-density component is melt-kneaded multiple times. Specifically, when the polyethylene composition containing the low-density component and the high-density component is melt-kneaded, the two components are sufficiently mixed by extruding in two stages using a twin-screw extruder and a single-screw extruder, and the entanglement of the polyethylene composition tends to be strong. Furthermore, as a method for improving the dispersibility of the polyethylene composition in the extrusion step, there is a method of adding a low-density component during the production step of the high-density component and melt-kneading them. Specifically, by adding a low-density component to a polyethylene powder of a high-density component produced by slurry polymerization and melt-kneading them, both components are thoroughly mixed, and the dispersibility of the polyethylene composition tends to be improved. Furthermore, in the initial stage of melt kneading, if the crystallinity of the high density component is close to that of the low density polyethylene, the long chain branches of the low density component are easily incorporated into the high density component, so that the two components are thoroughly mixed and the dispersibility of the polyethylene composition tends to improve. For example, the temperature of the solvent used in polymerizing the high density component is set to a temperature equal to or lower than 1 / 2 of the polymerization temperature, and the polymer powder is rapidly cooled to reduce the crystallinity, which tends to improve the affinity with the low density component. The polyethylene powder of the high density component thus obtained and the low density component are melt kneaded, so that the low density component and the high density component tend to be easily dispersed.

[0040] (Pulse NMR measurement at 180℃) As shown in the above <Condition (E)>, the polyethylene composition of the present embodiment has a relaxation time T α is 5 ms or more and 25 ms or less, and the presence ratio R of the low-motion component α α is preferably 25% or more and 55% or less. The relaxation time T of the low-mobility component α α is more preferably 8 ms or more, and even more preferably 10 ms or more, and is more preferably 23 ms or less, and even more preferably 20 ms or less. The proportion of low-mobility component α R α is more preferably 27% or more, and even more preferably 30% or more, and is more preferably 52% or less, and even more preferably 50% or less.

[0041] When the polyethylene composition of the present embodiment is subjected to pulse NMR at 180°C and the free induction decay curve obtained by the CPMG method is approximated as a three-component curve, the low mobility component α corresponds to a portion in the polyethylene composition in a molten state where the molecular chains are tightly entangled, and is considered to be a component that is likely to remain in the molded product without being unraveled during the molding process. α When the molecular chains are entangled to maintain the crystallinity of the polyethylene composition, the polyethylene composition has sufficient strength when treated at high temperatures, and the amount of elution of low-density components is reduced, so that a surface protection film and the like using the polyethylene composition of the present embodiment is preferably formed to have reduced adhesive residue on an adherend. On the other hand, the proportion of low-mobility components α R α When the polyolefin copolymer has a molecular weight of 55% or less, the stress generated when the polyethylene composition of the present embodiment is molded into a film is reduced, the film-forming processability is stabilized, and film breakage and wrinkles during high-speed processing can be reduced, which is preferable.

[0042] In addition, the relaxation time T α is an index showing the degree of constraint of the molecular chains of the low mobility component. The shorter the relaxation time in pulsed NMR measurements, the more the molecular chains are constrained and the stronger the entanglement in the molten state. The relaxation time T of the low-motion component α α When the time is 5 ms or more, the stress during molding and processing into a film is reduced, the film forming processability is stable, neck-in is small, and film breakage and wrinkles can be reduced, which is preferable. The relaxation time T of the low-motion component α α When the time t is 25 ms or less, the crystallinity of the polyethylene composition is maintained by entanglement of molecular chains, thereby providing sufficient stiffness during high-temperature processing, and reducing the amount of elution of low-density components and thus reducing adhesive residue on the adherend, which is preferable.

[0043] The relaxation time T of the low mobility component α of the polyethylene composition of the present embodiment described above α and the proportion R αcan be controlled within the above-mentioned numerical range, for example, by adjusting the compositional ratio of high density component and low density component in the polyethylene composition or by adjusting the synthesis conditions or polymerization conditions of the polymerization catalyst to adjust the molecular growth of polyethylene. For example, there may be mentioned a method in which the number of times that active species is supported during synthesis of the polymerization catalyst is set to a certain number or more, or a method in which a low-density component having an appropriate structure with high molecular weight long chain branches is contained in the polyethylene composition.

[0044] Specifically, the pulse NMR measurement applied to the measurement of the polyethylene composition of the present embodiment can be carried out by the following method. First, a sample tube filled with the polyethylene composition to a height of 1 cm from the bottom is placed in a Bruker TD-NMR apparatus (model: minispec mq20) set to give an internal temperature of the sample tube of 30°C, and the sample tube is heated in accordance with the <heating conditions> shown below. The temperatures shown in the <Heating Conditions> below are values ​​obtained by measuring the internal temperature of the sample with a thermocouple. <Heating conditions> (1) Set the temperature to 30°C and leave it for 5 minutes. (2) Raise the temperature to 180°C at a rate of 5°C / min. (3) Heat to 180°C and leave to stand for 25 minutes.

[0045] After the temperature increase is completed by the above-mentioned procedure, the spin-spin relaxation time (T2, sometimes simply referred to as "relaxation time T" in this specification) of polyethylene is measured according to the <measurement conditions> shown below. <Measurement conditions> Magnetic field strength: 0.47T Measured nuclides: 1 H(20MHz) Measurement method: Carr Purcell Meiboom Gill method Number of times accumulated: 256 Repeat time: 3 seconds Interval between the first 90° pulse and the 180° pulse (τ): 0.04 ms Total number of echo signals: 6400 The free induction decay (FID) obtained by the above-mentioned measurement is subjected to curve fitting using the analysis program TD-NMR-A manufactured by Bruker. For fitting, the function shown in the following Equation 1 is used. <Expression 1> f(t)=R α eXp(-t / T α )+R β eXp(-t / T β )+R γ eXp(-t / T γ ) (However, R α +R β +R γ = 100) t: variable (time elapsed since pulse irradiation) T α : Relaxation time of low-mobility component α (ms) R α : Proportion of low-mobility component α (%) T β : Relaxation time of intermediate component β (ms) R β : Presence ratio of intermediate component β (%) T γ : Relaxation time of the high-mobility component gamma (ms) R γ : Proportion of highly mobile component γ (%)

[0046] In general, for polymers in a rubbery state where the molecular chains are actively moving, the free induction decay obtained by pulsed NMR measurement can be expressed by an exponential function. Therefore, in this measurement, the free induction decay obtained can be fitted as the sum of three different components expressed by exponential functions, as shown in the above <Equation 1>. The decay rate of free induction decay is 1 It is known that the higher the mobility of H, i.e., the higher the mobility of the molecular chain, the slower the rate. The relaxation time T in each exponential function is T α <T β <T γ Therefore, the component with the lowest mobility is designated as α, the component with intermediate mobility as β, and the component with the highest mobility as γ. Furthermore, component α corresponds to a portion in which the molecular chains are strongly entangled in the polyethylene composition, component β corresponds to a portion in which the molecular chains are weakly entangled, and component γ corresponds to a portion in which the molecular chains are not entangled. More specifically, the pulse NMR measurement at 180° C. in this embodiment can be performed by the method described in the Examples.

[0047] (Mass ratio of components that dissolve at 80℃ or less) As shown in the above <Condition (F)>, in the polyethylene composition of the present embodiment, the mass proportion of components eluted up to 80°C in temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC), calculated from an elution temperature-elution amount curve obtained by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC) measurement, is preferably 1% by mass or more and 35% by mass or less of the total eluted amount, more preferably 2% by mass or more, and even more preferably 5% by mass or more, and still more preferably 30% by mass or less, and even more preferably 25% by mass or less. The "total amount of eluted" refers to the total area of ​​the elution temperature-elution amount curve in the range of 40°C to 120°C, and the mass proportion of the components eluting at 80°C or lower tends to be almost equal to the mass proportion of the low-density component contained in the polyethylene composition. When the mass ratio of the components eluted at 80°C or lower is 1 mass% or more of the total elution amount, stress due to the entanglement effect of the long-chain branched components acts in the kneading process in the extruder, improving the stability of film formation and reducing neck-in, which is preferable. By making the mass ratio of components eluted at 80° C. or less 35% by mass or less of the total eluted amount, the amount of components eluted during high-temperature processing is small, and adhesive residue is suppressed, which is preferable. The mass proportion of the components eluting at 80°C or lower can be controlled within the above-mentioned numerical range by adjusting the amount of the low-density components in the polyethylene composition. For example, the content of high-pressure low-density polyethylene in the ethylene resin composition may be controlled to be 1% by mass or more and 35% by mass or less. The CFC measurement applied to the measurement of the polyethylene composition of the present embodiment can be carried out, for example, by the method in the Examples.

[0048] (Ratio of low mobility components in low density polyethylene (B) at 180℃) As shown in the above <Condition (G)>, the polyethylene composition of the present embodiment has a density of 942 kg / m 3 and high-density polyethylene (A) having a density of 930 kg / m 3 A preferred embodiment is a mixture of the following low density polyethylenes (B): The low-density polyethylene (B) is characterized in that, when a free induction decay curve obtained by the CPMG method is approximated by three components in a pulse NMR measurement at 180° C., the presence ratio R α and the abundance ratio R of intermediate component β β It is preferable that the low mobility component ratio calculated by the following formula (I) is 0.35 or more and 0.55 or less. (Low Motility Component Ratio) = R α / (R α +R β ) (Formula I) The low mobility component ratio is more preferably 0.38 or more, and even more preferably 0.40 or more. Also, it is more preferably 0.53 or less, and even more preferably 0.50 or less.

[0049] The low mobility component ratio calculated by the formula (I) indicates the ratio of components having strong entanglement in a state in which the molecular chains are bound. Low-density polyethylene containing a large amount of such components is bound by entanglement and molecular motion is suppressed, so that it tends to suppress the promotion of crystalline melting of high-density components. Therefore, when the low mobility component ratio is 0.35 or more, the entanglement tends to suppress the promotion of crystalline melting of high-density components, so that the film has sufficient strength when treated at high temperatures, the amount of elution of low-density components is reduced, and the adhesive residue on the adherend is reduced in the surface protection film using the polyethylene composition of this embodiment, which is preferable. On the other hand, when the low mobility component ratio is 0.55 or less, the film forming processability of the film of the polyethylene composition of this embodiment is stable, and film breakage and wrinkles during high-speed processing can be reduced, which is preferable.

[0050] In the polyethylene composition of the present embodiment, the low mobility component proportion of the low-density polyethylene (B) calculated by the above formula (I) can be controlled within the above numerical range by controlling the amount of long chain branched structures by adjusting polymerization conditions such as the polymerization temperature, polymerization pressure, type of initiator, and type of chain transfer agent. For example, by adopting a method that does not use a chain transfer agent or a method that produces low-density polyethylene under forced stirring conditions, the starting point of radical polymerization tends to occur easily, the product has many long-chain branched structures, and the ratio of low-mobility components tends to be high. Also, by increasing the separation temperature and appropriately controlling the residence time in a high-pressure separator for unreacted ethylene gas, the bonding reaction between polyethylene molecules tends to occur easily, and because the residence time is controlled, decomposition of polyethylene does not occur, so a branched structure spreading in a dendritic shape is generated, and the ratio of low-mobility components tends to be high.

[0051] (Ratio of low mobility components in high density polyethylene (A) at 180℃) As shown in the above <Condition (H)>, the polyethylene composition of the present embodiment has a density of 942 kg / m 3 High density polyethylene (A) with a density of 930 kg / m 3 A preferred embodiment is a mixture of the following low density polyethylenes (B): When the high-density polyethylene (A) is measured by pulse NMR at 180° C., when the free induction decay curve obtained by the CPMG method is approximated as three components, the presence ratio R of the low mobility component α is α and the abundance ratio R of intermediate component β β It is preferable that the low mobility component ratio calculated by the following formula (I) is 0.50 or more and 0.70 or less. (Low Motility Component Ratio) = R α / (R α +R β ) (Formula I) It is more preferably 0.52 or more, and even more preferably 0.55 or more, and more preferably 0.68 or less, and even more preferably 0.65 or less.

[0052] The proportion of the low mobility component α indicates the proportion of components having strong entanglements in a state in which the molecular chains are constrained. In the high-density polyethylene (A), it is preferable that the ratio of low mobility components calculated by the above formula (I) is 0.50 or more, since the crystals of the polyethylene composition are maintained by entanglement, and sufficient strength is obtained when treated at high temperatures. On the other hand, when the ratio of low mobility components in the high-density polyethylene (A) is 0.70 or less, the high-density polyethylene (A) is easily entangled with the low-density polyethylene (B), which is preferable because the film-forming processability of the polyethylene composition of the present embodiment is stable and film breakage and wrinkles can be reduced. The proportion of low mobility components in the high density polyethylene (A) can be controlled within the above-mentioned range by adjusting the polymerization conditions such as synthesis conditions of the polymerization catalyst, polymerization temperature, polymerization pressure, comonomer type, etc., and thereby adjusting the molecular growth of polyethylene. For example, by adjusting the number of times of supporting active species during the production of the polymerization catalyst to increase the supporting concentration, the growing points of polyethylene on the catalyst surface become dense and have a plurality of active species, which tends to promote entanglement during the polyethylene growth process.

[0053] (High density polyethylene (A) and low density polyethylene (B) content) The polyethylene composition of the present embodiment has a density of 942 kg / m 3 High density polyethylene (A) with a density of 930 kg / m 3 In the case of a mixture containing the following low-density polyethylene (B), it is preferable that the content of the high-density polyethylene (A) is from 70% by mass to 99% by mass, and the content of the low-density polyethylene (B) is from 1% by mass to 30% by mass. When the abundance ratio of the high-density polyethylene (A) and the low-density polyethylene (B) is within the above range, a polyethylene composition having an excellent balance between stiffness during high-temperature processing of the film, adhesive residue during high-temperature processing of the adherend, and film-forming processability of the film can be obtained. More preferably, the content of the high-density polyethylene (A) is from 73% by mass to 97% by mass, and the content of the low-density polyethylene (B) is from 3% by mass to 27% by mass. More preferably, the content of the high density polyethylene (A) is from 75% by mass to 95% by mass, and the content of the low density polyethylene (B) is from 5% by mass to 25% by mass.

[0054] [Method for producing polyethylene composition] The method for producing the polyethylene composition of the present embodiment is not particularly limited, and examples thereof include a method in which a high density component and a low density component are contained by connecting a plurality of polymerization reactors, and a method in which a high density component and a low density component are produced separately and mixed. In particular, a method in which a high density polyethylene (A) and a low density polyethylene (B) produced by a high pressure method are mixed in advance and melt-kneaded is preferred. Here, high density polyethylene resin has a density of 942 kg / m 3 Low density polyethylene has a density of 930 kg / m or more. 3 The following is the result.

[0055] The method of premixing the high density polyethylene (A) and the low density polyethylene (B) is not particularly limited, but examples thereof include a method of pre-pelletizing the high density polyethylene (A) and the low density polyethylene (B) produced by a high pressure method, respectively, and dry blending the pellets, and a method of adding the pelletized low density polyethylene (B) to the powdered high density polyethylene (A) in the production process of the high density polyethylene (A). In particular, from the viewpoint of improving dispersibility, a method of performing dry blending for 1 hour or more is preferable. In addition, by adding the pelletized low density polyethylene (B) to the powdered high density polyethylene (A), the high density polyethylene (A) is mixed in a state of low crystallinity, so that the melting point of the high density polyethylene is lowered and it is easily mixed with the low density polyethylene (B), which is preferable.

[0056] As the melt kneader in the kneading operation, for example, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used. In particular, melt kneading in two stages using a twin screw extruder and a single screw extruder is preferred because the high density polyethylene (A) and the low density polyethylene (B) are easily dispersed.

[0057] The high-density polyethylene (A) can be produced, for example, by a continuous slurry polymerization method. The catalyst used in the production is not particularly limited, and for example, a metallocene catalyst, a Ziegler-Natta catalyst, a Phillips catalyst, etc. can be used. In particular, it is preferable to use a Ziegler-Natta catalyst having a plurality of active sites, since it promotes entanglement during molecular growth.

[0058] The Ziegler-Natta catalyst used in the production of the high-density polyethylene (A) is not particularly limited, but an olefin polymerization catalyst produced by supporting an organomagnesium compound and a titanium compound on a support prepared by reacting an organomagnesium compound with a chlorinating agent is preferred. The amount of the titanium compound that serves as the active site is not particularly limited, but from the viewpoint of increasing the amount supported in the pores of the support, the molar ratio of titanium to magnesium atoms contained in the support (Ti / Mg) is preferably 0.1 or more and 20 or less, and more preferably 0.2 or more and 10 or less. The method of supporting the titanium compound on the support is not particularly limited, and may be a method of reacting an excess titanium compound with the support, or a method of efficiently supporting the titanium compound by using a third component. In particular, from the viewpoint of increasing the concentration of the titanium compound supported on the support surface and promoting entanglement during molecular growth, a method of performing the supporting operation in multiple steps is preferred when supporting the titanium compound, and more preferably, the number of times of supporting is two, and the molar ratio of the active species added in each supporting operation is set to 1:3 (first supporting operation: second supporting operation).

[0059] In general, physical properties such as molecular weight and density can be controlled by adjusting the polymerization temperature, polymerization pressure, comonomer concentration, and hydrogen concentration in addition to the catalyst type.

[0060] Comonomers that can be used in the production of the polyethylene composition of the present embodiment are not particularly limited, and examples thereof include compounds selected from the group consisting of propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, vinylcyclohexane, styrene, and derivatives thereof; cyclopentene, cycloheptene, and the like. and linear, branched, or cyclic dienes having 4 to 20 carbon atoms selected from the group consisting of 1,3-butadiene, 1,4-pentadiene, 1,5-hexadiene, 1,4-hexadiene, 1,7-octadiene, and cyclohexadiene. In particular, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and the like are preferred, and the density of the high-density polyethylene can be adjusted by appropriately controlling the type and concentration of the comonomer.

[0061] The polymerization temperature is preferably 30°C or higher and 100°C or lower. A polymerization temperature of 30°C or higher allows for more efficient industrial production, while a polymerization temperature of 100°C or lower allows for more stable continuous operation.

[0062] The solvent used in the continuous slurry polymerization process may be an inert hydrocarbon medium, or the olefin itself may be used as the solvent. Examples of the inert hydrocarbon medium include, but are not limited to, aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, and dichloromethane, and mixtures thereof. The temperature of the solvent supplied into the polymerization system is not particularly limited, but from the viewpoint of reducing the crystallinity of the resulting high-density polyethylene (A) powder and improving the affinity with the low-density component, it is preferable to set the temperature at not more than half the polymerization temperature.

[0063] The polymerization pressure in the production method for the high-density polyethylene (A) of the present embodiment is usually preferably from normal pressure to 2 MPa, more preferably from 0.1 MPa to 1.5 MPa, and even more preferably from 0.1 MPa to 1.0 MPa.

[0064] The molecular weight of the high-density polyethylene (A) used in the polyethylene composition of the present embodiment can be adjusted by making hydrogen present in the polymerization system or by changing the polymerization temperature, as described in German Patent Application Publication No. 3127133. The molecular weight can be controlled within an appropriate range by adding hydrogen as a chain transfer agent to the polymerization system. Examples of the solvent separation method include decantation, centrifugation, and filtration. Centrifugation is more preferred because it provides a good separation efficiency between the ethylene polymer and the solvent. The polymer powder is granulated into pellets by a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. The type of extruder and the number of extrusions are not particularly limited, but kneading by a twin screw extruder is preferred.

[0065] The high-pressure low-density polyethylene (B) used in the polyethylene composition of the present embodiment can be obtained by radical polymerization of ethylene in, for example, an autoclave-type or tubular-type reactor, although this is not limited thereto. When an autoclave type reactor is used, the polymerization conditions may be set to a temperature of 200 to 300°C and a polymerization pressure of 100 to 250 MPa in the presence of a peroxide, while when a tubular type reactor is used, the polymerization conditions may be set to a polymerization reaction peak temperature of 180 to 400°C and a polymerization pressure of 100 to 400 MPa in the presence of a peroxide. In particular, the method of polymerization using an autoclave type reactor is preferred because the long chain branching reaction is promoted by forced stirring. The molecular weight, density, molecular weight distribution, and molecular structure of the obtained low-density polyethylene are controlled by the polymerization temperature, polymerization pressure, type of peroxide, and the presence or absence of a chain transfer agent. In general, setting the polymerization pressure high tends to increase the molecular weight, while setting the polymerization pressure low tends to decrease the molecular weight. In addition, the addition of a chain transfer agent can suppress the branching reaction, so that the density tends to increase and the molecular weight tends to decrease.

[0066] The peroxides are not limited to the following, but examples thereof include methyl ethyl ketone peroxide, peroxyketals (specifically, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)octane, n-butyl 4,4-bis(t-butylperoxy)valerate, 2,2-bis(t-butylperoxy)butane, etc.), hydroperoxides (specifically, t-butyl hydroperoxy, -oxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, etc.), dialkyl peroxides (specifically, di-t-butyl peroxide, dicumyl peroxide, bis(t-butylperoxyisopropyl)benzene, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyldi(t-butyl peroxydicarbonates (specifically, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, dimethoxy ... Diisopropyl peroxydicarbonate, di(3-methyl-3-methoxybutyl peroxydicarbonate, diallyl peroxydicarbonate, etc.), peroxyesters (specifically, t-butyl peroxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxypivalate, t-butyl peroxyoctate, t-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxy-3,5,6-trimethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl carbonate, cumyl peroxyoctoate, t-hexyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxyneohexanoate, t-hexyl peroxyneohexanoate, cumyl peroxyneohexanoate, etc.), acetylcyclohexylsulfonyl peroxide, t-butyl peroxyallyl carbonate, etc., It is particularly preferable to select a highly reactive peroxide, for example, a peroxy ester (specifically, t-butyl peroxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxypivalate, t-butyl peroxyoctate, t-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxy-3,5,6-trimethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl carbonate, cumyl peroxyoctoate, t-hexyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxyneohexanoate, t-hexyl peroxyneohexanoate, cumyl peroxyneohexanoate, etc.), since this promotes the long-chain branching reaction.

[0067] The chain transfer agent is not particularly limited, but for example, a hydrocarbon compound such as propane, propylene, or butane is used, and various physical properties can be adjusted by terminating the radicals of the growing polymer. In particular, polymerization without using a chain transfer agent is preferable because it produces a polymer with a higher degree of polymerization and many long chain branches.

[0068] The low-density polyethylene polymerized in the reactor is separated into unreacted ethylene gas components and polymer components by a gas separation device adjusted to an arbitrary pressure. Multiple gas separation devices may be connected together, and from the viewpoint of safety, it is common to install two or more gas separation devices. In addition, the temperature of the gas separation device and the residence time of the low-density polyethylene in the gas separator affect the long-chain branching structure and the degree of decomposition of the low-density polyethylene. In particular, since unreacted peroxides and radicals remain in the low-density polyethylene present in the gas separation device immediately after the reactor, it is preferable to set the temperature of the gas separation device immediately after the reactor to 220°C or higher and 260°C or lower and the residence time to 20 minutes or less, so that the unreacted gas is immediately separated, the bonding between polyethylene chains is promoted, and decomposition of the polymer chains due to deterioration does not occur, and therefore a high-pressure low-density polyethylene having a long-chain branching structure with a high molecular weight tends to be produced.

[0069] (Additives) The polyethylene composition of the present embodiment, each of the raw material components, and the molded article may further contain additives such as an antioxidant, a light resistance stabilizer, a slip agent, a filler, an antistatic agent, etc.

[0070] [Molded body] The molded article of the present embodiment is a molded article of the polyethylene composition of the present embodiment described above. Examples of the molded article of the present embodiment include films. When the film is a multilayer film, the polyethylene composition of the present embodiment may be used in the outermost layer or in an intermediate layer. Specific applications of the film include surface protection films for optical members and the like. EXAMPLES

[0071] The present embodiment will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited in any way to the following examples and comparative examples. The measurement and evaluation methods for each physical property and characteristic are described below. Unless otherwise specified, the measurements and evaluations were carried out at room temperature.

[0072] [Methods for measuring physical properties] (Physical property 1) Melt flow rate (MFR) at 190℃ and a load of 2.16 kg) For each of the polyethylene compositions obtained in the Examples and Comparative Examples, and the high-density polyethylene (A) and low-density polyethylene (B) used as raw materials, the melt flow rate (g / 10 min) was measured in accordance with JIS K7210 Code D:1999 (temperature = 190°C, load = 2.16 kg).

[0073] ((Property 2) Density) The density (kg / m) of each polyethylene composition obtained in the examples and comparative examples, and the high-density polyethylene (A) and the low-density polyethylene (B) used as raw materials were measured by the density gradient tube method (23°C) according to JIS K7112:1999. 3 ) was measured.

[0074] (Physical Property 3) Weight average molecular weight measured by GPC For each of the polyethylene compositions obtained in the Examples and Comparative Examples, gel permeation chromatography (GPC) was measured using a GPC-IR manufactured by Polymer Char Corporation and an IR5 manufactured by Polymer Char Corporation as a detector. A sample solution was prepared by introducing 15 mL of o-dichlorobenzene as a mobile phase into 20 mg of each of the polyethylene compositions obtained in the Examples and Comparative Examples and stirring at 150° C. for 1 hour, and allowed to flow at a flow rate of 1.0 mL / min. A UT-807 (one column) manufactured by Showa Denko K.K. and GMHHR-H(S)HT (two columns) manufactured by Tosoh Corporation were used in series, and measurements were performed under conditions of a column temperature of 140° C., a sample dissolution temperature of 140° C., and a sample dissolution time of 90 minutes. The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) determined by GPC was taken as the molecular weight distribution. Molecular weight calibration was performed at 12 points in the range of 1,050 to 2,060,000 for the molecular weight (Mw) of standard polystyrene manufactured by Tosoh Corporation. The Mw of each standard polystyrene was multiplied by a coefficient of 0.43 to obtain the polyethylene-equivalent molecular weight. A primary calibration line was created from a plot of elution time versus polyethylene-equivalent molecular weight to determine the weight-average molecular weight (Mw) and number-average molecular weight (Mn).

[0075] (Physical Property 4) Crystallinity and crystallite size measured by wide-angle X-ray scattering (WAXS) The degree of crystallinity and crystallite size of each of the polyethylene compositions obtained in the Examples and Comparative Examples were measured by transmission wide-angle X-ray scattering measurement using a transmission X-ray scattering apparatus NANOPIX manufactured by Rigaku Corporation. A sample cut to a thickness of 1 mm was irradiated with Cu-Kα radiation, and scattering was detected using a semiconductor detector HypiX-6000. The sample-detector distance was 96 mm, the output was 40 kV, 30 mA, the exposure time was 5 seconds, and the environment around the sample cell was under vacuum conditions. The optical system used was a point focus, and measurements were performed under the following conditions: 1st slit: φ=0.55 mm, 2nd slit: open, Guard slit: φ=0.35 mm. In the case of transmission wide-angle X-ray scattering measurement, in the X-ray scattering pattern obtained by the two-dimensional detector, when the position where the X-ray irradiated to the sample travels straight through the sample, passes through the sample, and reaches the two-dimensional detector is the center, the scattering intensity at the same distance from the center corresponds to the same scattering angle. Therefore, by calculating the intensity average at each scattering angle for the measured X-ray scattering pattern (circular average), a one-dimensional scattering intensity profile for the scattering angle 2θ can be obtained. In the range of 2θ=10.0° to 2θ=29.0° of the obtained one-dimensional profile, a process was performed to separate the diffraction peak of the orthorhombic (110) plane of polyethylene, the diffraction peak of the orthorhombic (200) plane of polyethylene, and the amorphous peak of polyethylene. A baseline was drawn connecting 2θ=10.0° to 2θ=29.0° in a straight line, and the (110) and (200) diffraction peaks of polyethylene were approximated by a Voigt function, and the amorphous peak of polyethylene was approximated by a Gaussian function. The peak position of the amorphous peak was fixed at 2θ=19.6° and the full width at half maximum was fixed at 3.8°, while the peak position and full width at half maximum of the crystalline peak were not particularly fixed, and peak separation was performed. The crystallite size (D) was calculated from the full width at half maximum of the (110) diffraction peak of polyethylene calculated by peak separation according to Scherrer's formula (below). The degree of crystallinity was obtained as a percentage of the area of ​​the crystalline peak relative to the sum of the areas of the separated crystalline peak and amorphous peak. D=Kλ / (βcosθ) (Scherrer formula) D: Crystallite size (nm) K: 0.9 (constant) λ: wavelength of X-rays (nm) β:(β1 2 -β2 2 ) 0.5 β1: Full width at half maximum (rad) of the (hkl) peak calculated as a result of peak separation β2: Full width at half maximum of the incident beam divergence (rad) θ: Bragg angle

[0076] (Physical Property 5) Y / X in Temperature Variable Wide Angle X-ray Scattering (WAXS) Measurements Variable-temperature WAXS measurement of each of the polyethylene compositions obtained in the Examples and Comparative Examples was carried out using a transmission type X-ray scattering instrument NANOPIX manufactured by Rigaku Corporation. A sample cut to a thickness of 1 mm was irradiated with Cu-Kα radiation, and scattering was detected using a semiconductor detector HypiX-6000. The measurement was performed under the following conditions: sample-detector distance: 96 mm; output: 40 kV, 30 mA; exposure time: 10 seconds; and the environment around the sample cell was in vacuum. The optical system was a point focus, and the slit diameters were 1st slit: φ=0.55 mm, 2nd slit: open, and guard slit: φ=0.35 mm. The sample was placed on the heating stage and held at 50°C for 10 minutes to equalize the temperature of the stage and sample. The temperature was then increased at a rate of 2°C per minute, and WAXS measurements were performed at each temperature. In the X-ray scattering pattern obtained by the 2D detector, when the X-rays irradiated to the sample travel straight through the sample, pass through the sample, and reach the 2D detector, the scattering intensity at the same distance from the center corresponds to the same scattering angle. Therefore, by calculating the average intensity at each scattering angle for the measured X-ray scattering pattern (circular average), a 1D scattering intensity profile for the scattering angle 2θ can be obtained. In the range of 2θ=10.0° to 2θ=29.0° of the obtained 1D profile, a process was performed to separate the diffraction peak of the orthorhombic (110) plane of polyethylene, the diffraction peak of the orthorhombic (200) plane of polyethylene, and the amorphous peak of polyethylene. A baseline was drawn connecting 2θ=10.0° to 2θ=29.0° in a straight line, and the (110) and (200) diffraction peaks of polyethylene were approximated by a Voigt function, and the amorphous peak of polyethylene was approximated by a Gaussian function. The peak position of the amorphous peak was fixed at 2θ=19.6° and the full width at half maximum was fixed at 3.8°, while the peak position and full width at half maximum of the crystalline peak were not particularly fixed, and peak separation was performed. Regarding the peak intensity originating from the (110) plane in the one-dimensional profile at each temperature obtained by the above measurement, the ratio of the peak intensity X originating from the (110) plane at 50°C to the peak intensity Y originating from the (110) plane at 130°C was calculated as Y / X.

[0077] (Physical Properties 6) Pulse NMR measurement at 180℃, relaxation time T α (ms), the proportion of low-mobility component α R α , the proportion of intermediate component β R β , low-motile component ratio) Pulsed NMR measurements of each of the polyethylene compositions obtained in the Examples and Comparative Examples, and the high-density polyethylene (A) and low-density polyethylene (B) used as raw materials were carried out as follows. First, a sample tube filled with the sample to a height of 1 cm from the bottom was placed in a Bruker TD-NMR device (model: minispec mq20) set to an internal temperature of the sample tube of 30°C, and the sample tube was heated according to the heating conditions shown below. The temperatures shown in the following <Heating Conditions> are values ​​obtained by measuring the internal temperature of the sample with a thermocouple. <Heating conditions> (1) Set the temperature to 30°C and leave it for 5 minutes. (2) Raise the temperature to 180°C at a rate of 5°C / min. (3) Heat to 180°C and leave to stand for 25 minutes. After the temperature increase was completed by the above procedure, the spin-spin relaxation time (T2, sometimes simply referred to as "relaxation time" in this specification) of the sample was measured according to the <measurement conditions> shown below. <Measurement conditions> Magnetic field strength: 0.47T Measured nuclides: 1 H(20MHz) Measurement method: Carr Purcell Meiboom Gill method Number of times accumulated: 256 Repeat time: 3 seconds Interval between the first 90° pulse and the 180° pulse (τ): 0.04 ms Total number of echo signals: 6400 The free induction decay (FID) obtained by the above measurement was subjected to curve fitting using the analysis program TD-NMR-A manufactured by Bruker. For fitting, the function shown in the following Equation 1 was used. <Expression 1> f(t)=R α eXp(-t / T α )+R β eXp(-t / T β )+R γ eXp(-t / T γ ) (However, R α +R β +R γ = 100) t: variable (time elapsed since pulse irradiation) T α : Relaxation time of low-mobility component α (ms) R α : Proportion of low-mobility component α (%) T β : Relaxation time of intermediate component β (ms) R β : Presence ratio of intermediate component β (%) T γ : Relaxation time of the high-mobility component gamma (ms) R γ : Proportion of highly mobile component γ (%) By curve fitting of the free induction decay, the abundance ratio R of the low mobility component α in each of the polyethylene compositions obtained in the examples and comparative examples was calculated. α , the relaxation time T of the low-mobility component α α was calculated. Furthermore, for the raw materials of each of the polyethylene compositions obtained in the Examples and Comparative Examples, the ratio of low mobility components was calculated from the relaxation time T and the abundance ratio R obtained by the same method as above, according to the following (Equation I). (Low Motility Component Ratio) = R α / (R α +R β ) (Formula I)

[0078] (Physical Property 7) Elution temperature-elution amount curve in cross fractionation chromatography (CFC) measurement, mass ratio of components eluted at 80°C or less to the total elution amount) For each of the polyethylene compositions obtained in the examples and comparative examples, CFC measurement was carried out using an Automated 3D analyzer CFC-2 manufactured by Polymer ChAR. A stainless steel microball column (outer diameter 3 / 8 inch × length 150 mm) was used as the TREF column. A total of three GPC columns were used: one GPC UT-807 manufactured by ShodeX and two GMHHR-H(S)HT manufactured by Tosoh Corporation. As an eluent, o-dichlorobenzene (for high performance liquid chromatography) was flowed at a flow rate of 1.0 mL / min. The column containing the packing material was heated to 140° C., and 20 mL of a sample solution (sample concentration: 1.0 g / mL) prepared by dissolving a polyethylene composition in o-dichlorobenzene was introduced and maintained for 120 minutes. Next, the temperature of the column was lowered to 40° C. at a rate of 0.5° C. / min, and then held at that temperature for 20 minutes. During this process, the sample was precipitated on the packing surface. The column temperature was then adjusted as follows: First, the temperature was raised to 50°C and held at 50°C. Next, the temperature was raised to 60°C and held at 60°C. Furthermore, the temperature was raised from 60°C to 75°C at 5°C intervals, raised from 75°C to 90°C at 3°C ​​intervals, raised from 90°C to 110°C at 1°C intervals, and held at 5°C intervals from 110°C to 120°C. The temperature was raised at a rate of 20°C / min during each heating process, and each temperature was held for 21 minutes. The concentration (mass%) of the sample dissolved during 21 minutes at each holding temperature was detected, and a dissolution temperature-dissolution amount curve was obtained from the holding temperature and the dissolution sample concentration. Furthermore, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the components eluted during 21 minutes of retention at each retention temperature were determined using a GPC column connected to the TREF column. From the elution temperature-elution amount curve obtained as described above, the mass ratio of the components eluted at 80° C. or lower to the total eluted amount was calculated.

[0079] [Evaluation method] (Evaluation 1: Firmness during high-temperature processing) Each of the polyethylene compositions obtained in the Examples and Comparative Examples was molded using a T-die film forming machine (HM40N manufactured by Hokushin Sangyo Co., Ltd., screw diameter 40 mm, die width 300 mm) at a cylinder temperature of 200°C, a die temperature of 210°C, an extrusion rate of 5 kg / hour, an air gap of 10 cm, and a take-up speed of 9 m / min, and both ends were trimmed by 50 mm to obtain a film made of the polyethylene composition having a thickness of 35 μm. The obtained film was cut to a width of 10 cm and a length of 10 cm, and the midpoints of one pair of opposite sides were clipped to ensure that there were no wrinkles, and the film was fixed so that the distortion was 0% and the film was horizontal to the ground. In this state, an evaluation test of stiffness during high-temperature processing was conducted in an environment of 2 atm and 100% RH. The sample was placed in the oven under the above conditions and maintained for 5 minutes. The vertical distance from the lowest point of the film to the horizontal plane was taken as the distance L (cm) that the film sagged downward from the horizontal direction, and the stiffness during high-temperature processing was evaluated according to the following criteria. ◎: Less than 3cm ○: 3cm or more, less than 6cm △: 6cm or more but less than 9cm ×: 9cm or more or film breaks

[0080] (Evaluation 2: Residue after high-temperature processing) The film obtained in the above (Evaluation 1) was cut to a size of 5 cm wide x 5 cm long, and attached to a new slide glass measuring 7.6 cm wide x 2.6 cm long without trapping air bubbles, and the four corners were fixed with cellophane tape to prepare a sample. This sample was subjected to an evaluation test of residue after high-temperature processing in an environment of 130°C, 2 atm, and 100% RH. The sample was placed in the oven set under the above conditions, and after 60 minutes, the sample was removed. After 1 minute, the film was peeled off with tweezers, and the surface of the 5 cm wide x 2.6 cm long slide where the film and the slide were in contact was visually observed, and the residue after high-temperature processing was evaluated according to the following criteria. ⊚: No residue was observed within the observation area. ◯: Residue was observed in less than 20% of the observation area. △: Residue was observed in 20% or more and less than 40% of the observation area. ×: Residue was observed in 40% or more of the observation area.

[0081] ((Rating 3) Neck-in) To evaluate high-speed film formability, each of the polyethylene compositions obtained in the examples and comparative examples was molded using a T-die film forming machine (HM40N manufactured by Hokushin Sangyo Co., Ltd., screw diameter 40 mm, die width 300 mm) at a cylinder temperature of 200°C, a die temperature of 210°C, an extrusion rate of 5 kg / hour, an air gap of 10 cm, and a take-up speed of 20 m / min. The difference between the width of the obtained film and the width of the T-die was defined as neck-in (mm) and was evaluated according to the following criteria. Neck-in is an index of the processability of a film. The smaller the neck-in under high-speed conditions, the better the film processability, since it is possible to process the film into a thin film without film breakage and the higher the film yield. ◎: 50mm or less ○: More than 50mm~60mm or less △:More than 60mm~70mm or less ×: Over 70mm, or edge or membrane cut occurs

[0082] [Preparation of components used in the examples and comparative examples] (Catalyst Preparation) <Preparation of Ziegler-Natta catalyst (a-1)> In an 8 L stainless steel autoclave that had been thoroughly purged with nitrogen, 1,000 mL of a 2 mol / L hexane solution of hydroxytrichlorosilane was placed and stirred at 65°C while adding AlMg5(C4H9) 11 2,550 mL of a hexane solution of an organomagnesium compound represented by (OC4H9)2 (corresponding to 2.68 mol of magnesium) was added dropwise over 4 hours, and the reaction was continued with stirring at 65°C for another hour. After the reaction was completed, the supernatant was removed and the solid was washed four times with 1,800 mL of hexane to obtain a solid support. Analysis of this solid showed that it contained 8.31 mmol of magnesium per gram of solid. 1,970 mL of hexane slurry containing 110 g of the carrier was added with stirring at a temperature of 10° C. to 28 mL of 1 mol / L titanium tetrachloride hexane solution and 1 mol / L AlMg5(C4H9) 11 28 mL of a hexane solution of an organomagnesium compound represented by (OSiH)2 was added simultaneously over 1 hour. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed, and the residue was washed twice with 1100 mL of hexane. Next, 1100 mL of hexane was added to the washed solid, and 82 mL of 1 mol / L titanium tetrachloride hexane solution and 1 mol / L AlMg5(C4H9) 11 82 mL of a hexane solution of an organomagnesium compound represented by (OSiH)2 was added simultaneously over 1 hour. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed and the residue was washed twice with 1100 mL of hexane to prepare Ziegler-Natta catalyst (a-1).

[0083] <Preparation of Ziegler-Natta catalyst (a-2)> In an 8 L stainless steel autoclave that had been thoroughly purged with nitrogen, 1,000 mL of a 2 mol / L hexane solution of hydroxytrichlorosilane was placed and stirred at 65°C while adding AlMg5(C4H9) 11 2,550 mL of a hexane solution of an organomagnesium compound represented by (OC4H9)2 (corresponding to 2.68 mol of magnesium) was added dropwise over 4 hours, and the reaction was continued with stirring at 65°C for another hour. After the reaction was completed, the supernatant was removed and the solid was washed four times with 1,800 mL of hexane to obtain a solid support. Analysis of this solid showed that it contained 8.31 mmol of magnesium per gram of solid. 1,970 mL of hexane slurry containing 110 g of the carrier was added with stirring at a temperature of 10° C. to 82 mL of 1 mol / L titanium tetrachloride hexane solution and 1 mol / L AlMg5(C4H9) 11 82 mL of a hexane solution of an organomagnesium compound represented by (OSiH)2 was added simultaneously over 1 hour. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed and the solid was washed twice with 1100 mL of hexane. Next, 1100 mL of hexane was added to the washed solid, and 28 mL of 1 mol / L titanium tetrachloride hexane solution and 1 mol / L AlMg5(C4H9) 11 28 mL of a hexane solution of an organomagnesium compound represented by (OSiH)2 was added simultaneously over 1 hour. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed and the residue was washed twice with 1100 mL of hexane to prepare Ziegler-Natta catalyst (a-2).

[0084] <Preparation of Ziegler-Natta catalyst (a-3)> In an 8 L stainless steel autoclave that had been thoroughly purged with nitrogen, 1,000 mL of a 2 mol / L hexane solution of hydroxytrichlorosilane was placed and stirred at 65°C while adding AlMg5(C4H9) 112,550 mL of a hexane solution of an organomagnesium compound represented by (OC4H9)2 (corresponding to 2.68 mol of magnesium) was added dropwise over 4 hours, and the reaction was continued with stirring at 65°C for another hour. After the reaction was completed, the supernatant was removed and the solid was washed four times with 1,800 mL of hexane to obtain a solid support. Analysis of this solid showed that it contained 8.31 mmol of magnesium per gram of solid. 110 mL of hexane slurry containing 110 g of the carrier was added to 1,970 mL of hexane slurry containing 110 g of the carrier at a temperature of 10° C., and 110 mL of hexane solution containing 1 mol / L of titanium tetrachloride and 1 mol / L of AlMg5(C4H9) were added to the slurry. 11 110 mL of a hexane solution of an organomagnesium compound represented by (OSiH)2 was added simultaneously over 1 hour. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed, and the residue was washed twice with 1100 mL of hexane to prepare a Ziegler catalyst (a-3).

[0085] <Preparation of Ziegler-Natta catalyst (a-4)> In the same manner as in the method of Patent No. 6792957, a 200 mL stainless steel autoclave was filled with nitrogen and was charged with AlMg6(C4H9) 12 40 mL of a hexane solution of an organomagnesium compound represented by the formula (OC3H7)3 (corresponding to a total of 37.8 mmol of aluminum and magnesium) was charged, and 40 mL of hexane containing 2.27 g (37.8 mmol) of methylhydrogenpolysiloxane was added dropwise over 30 minutes while stirring at 25°C. After the dropwise addition, the temperature was raised to 80°C and the reaction was allowed to proceed with stirring for 3 hours to obtain an organomagnesium compound to be contacted with a titanium compound. An 8 L stainless steel autoclave that had been thoroughly purged with nitrogen was charged with 2400 mL of hexane, and the solution was stirred at -5°C while stirring to obtain an organomagnesium compound represented by the formula AlMg6(C4H9) 12 1300 mL of a hexane solution of an organomagnesium compound represented by (OC3H7)3 (corresponding to 521 mmol of magnesium) and 1300 mL of a hexane solution of 0.5 mol / L titanium tetrachloride were simultaneously added dropwise over a period of 2 hours. After the dropwise addition, the mixture was further aged at 10°C for 1 hour with stirring, the supernatant was removed, and the mixture was washed four times with 3000 mL of hexane to prepare Ziegler-Natta catalyst (a-4).

[0086] <Preparation of metallocene catalyst (b-1)> As in the method of Patent No. 6912290, 40 g of catalyst carrier silica (average particle size 15 μm, compressive strength 3 MPa) dehydrated at 600°C was dispersed in 800 mL of hexane in a 1.8 L autoclave under a nitrogen atmosphere to obtain a slurry. The obtained slurry was kept at 25°C and 84 mL of a hexane solution of triethylaluminum (concentration 1 mol / L) was added while stirring. After that, the mixture was stirred for 2 hours to react triethylaluminum with the surface hydroxyl groups of the silica, and a hexane slurry of component [a] in which the surface hydroxyl groups of the silica were capped with triethylaluminum was obtained. On the other hand, 200 mmol of [(Nt-butylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium dimethyl (hereinafter referred to as "titanium complex") was dissolved in 1000 mL of Isopar E (registered trademark) (a trade name for a hydrocarbon mixture manufactured by Exxon Chemical Company (USA)), 20 mL of a 1 mol / L hexane solution of n-butylethylmagnesium was added, and further hexane was added to adjust the titanium complex concentration to 0.1 mol / L, thereby obtaining component [b]. In addition, 5.7 g of bis(hydrogenated tallow alkyl)methylammonium-tris(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter referred to as "borate compound") was added and dissolved in 50 mL of toluene to obtain a 100 mmol / L toluene solution of the borate compound. 5 mL of a 1 mol / L hexane solution of diethylaluminum ethoxide was added to this toluene solution of the borate compound at room temperature, and further hexane was added so that the concentration of the borate compound in the solution became 70 mmol / L. After that, the mixture was stirred at room temperature for 1 hour to obtain a reaction mixture [c] containing the borate compound. The temperature of the component [a] slurry was raised to 45 to 50°C, and the stirring speed was set to 600 rpm. 9.2 mL of the reaction mixture [c] and 6.4 mL of the component [b] were simultaneously dropped into the hexane slurry of component [a] over a period of 20 minutes, and then the mixture was stirred at 50°C for 1 hour, thereby allowing the catalytically active species to penetrate into the silica. Then, the supernatant containing the unreacted borate compound-titanium complex in the obtained reaction mixture was removed by decantation, and the catalytically active species was supported inside the silica. After the temperature was lowered to 10-15°C, 36.8 mL of the reaction mixture [c] and 25.6 mL of the component [b] were simultaneously dropped over 80 minutes, and then the mixture was stirred at 15-20°C for 3 hours to react and precipitate the titanium complex and the borate, and the catalytically active species was physically adsorbed on the silica surface. Then, the supernatant containing the unreacted borate compound-titanium complex in the obtained reaction mixture was removed by decantation, and a supported geometrically constrained metallocene catalyst (b-1) in which the catalytically active species was formed on the silica surface and inside was obtained.

[0087] (High density polyethylene (A)) <Production of High Density Polyethylene (A-1)> A vessel-type 280L polymerization reactor equipped with an agitator was used to carry out continuous polymerization under the conditions of polymerization temperature 70°C, polymerization pressure 0.80MPa, and average residence time 1.6 hours. 40L / hour of dehydrated normal hexane was supplied as the solvent, 0.4g / hour of the Ziegler-Natta catalyst (a-1) as the catalyst, and 24mmol / hour of triisobutylaluminum as the liquid cocatalyst component in terms of Al atom. Ethylene was polymerized by supplying hydrogen for molecular weight control at 40.2mol% of the gas phase concentration of ethylene. Dehydrated normal hexane was supplied from the bottom of the polymerization reactor after being cooled to 10°C by a heat exchanger, and hydrogen was supplied from the catalyst introduction line from the middle between the liquid level and the bottom of the polymerization reactor together with the catalyst in advance to contact the catalyst, and ethylene was supplied from the bottom of the polymerization reactor. The polymerization slurry in the polymerization reactor was led to a flash tank at a pressure of 0.08 MPa and a temperature of 75° C. so that the level of the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated. Next, the polymerization slurry was continuously sent to a centrifuge so that the level of the polymerization reactor was kept constant, and the polymer was separated from the other components such as the solvent, etc. At that time, the content of the solvent, etc. relative to the polymer was 45% by mass. The separated high density polyethylene powder was dried at 85°C with nitrogen blowing. Next, 300 ppm by mass of pentaerythritol-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the obtained powder, thereby obtaining a powdered high-density polyethylene (A-1).

[0088] <Production of High Density Polyethylene (A-2)> High density polyethylene (A-2) was produced by the same operation as in the production of the high density polyethylene (A-1) except that the polymerization temperature was 70°C, the polymerization pressure was 1.0 MPa, the temperature of the dehydrated normal hexane was 50°C, the amount of hydrogen supplied was 28.6 mol% based on the gas phase ethylene concentration, and 1-butene was 0.58 mol% based on the gas phase ethylene concentration.

[0089] <Production of high density polyethylene (A-3)> A high density polyethylene (A-3) was obtained by the same operation as in the production of the high density polyethylene (A-1) except that the polymerization temperature was 65°C, the polymerization pressure was 1.0 MPa, the temperature of the dehydrated normal hexane was 30°C, and hydrogen was 61.3 mol% relative to the gas phase ethylene concentration.

[0090] <Production of High Density Polyethylene (A-4)> A high density polyethylene resin (A-4) was obtained by polymerization in the same manner as in the production of the high density polyethylene (A-1), except that a Ziegler-Natta catalyst (a-2) was used as the catalyst.

[0091] <Production of High Density Polyethylene (A-5)> A high density polyethylene resin (A-5) was obtained by polymerization in the same manner as in the production of the high density polyethylene (A-1), except that a Ziegler-Natta catalyst (a-3) was used as the catalyst.

[0092] <Production of High Density Polyethylene (A-6)> A Ziegler-Natta catalyst (a-2) was used as the catalyst, and the hydrogen was 40.2 mol% relative to the gas phase concentration of ethylene. Polymerization was carried out in the same manner as for the high density polyethylene (A-2), except that a high density polyethylene resin (A-6) was obtained.

[0093] <Production of High Density Polyethylene (A-7)> A Ziegler-Natta catalyst (a-3) was used as the catalyst, the polymerization temperature was 75°C, hydrogen was 54.3 mol% relative to the gas phase ethylene concentration, and 1-butene was not supplied. Except for this, polymerization was carried out in the same manner as for the high density polyethylene (A-2), to obtain a high density polyethylene resin (A-7).

[0094] <Production of High Density Polyethylene (A-8)> With reference to the method of Example (A-2) of Japanese Patent No. 6792957, a Ziegler-Natta catalyst (a-4) was used as the catalyst, and the polymerization temperature was set to 86°C. In the same manner as for the high-density polyethylene (A-2), polymerization was carried out to obtain a high-density polyethylene resin (A-8).

[0095] <Production of High Density Polyethylene (A-9)> With reference to the method of Example (A-4) of Japanese Patent No. 6912290, a vessel-type 340L polymerization reactor equipped with an agitator was used to carry out continuous polymerization under the conditions of polymerization temperature 80°C, polymerization pressure 0.98MPa, and average residence time 3.2 hours. 40L / hour of dehydrated normal hexane was supplied as the solvent, 1.4mmol / hour of the above metallocene catalyst (b-1) was supplied as the catalyst in terms of Ti atoms, and 20mol / hour of triisobutylaluminum was supplied as the liquid cocatalyst component in terms of Al atoms. Hydrogen for molecular weight control was supplied to be 0.47mol% relative to the gas phase concentration of ethylene, thereby polymerizing ethylene. Dehydrated normal hexane was supplied from the bottom of the polymerization reactor with its temperature adjusted to 50°C, and hydrogen was supplied from the catalyst introduction line from the middle between the liquid level and the bottom of the polymerization reactor together with the catalyst in order to contact the catalyst in advance, and ethylene was supplied from the bottom of the polymerization reactor. The polymerization slurry in the polymerization reactor was led to a flash tank at a pressure of 0.08 MPa and a temperature of 75° C. so that the level of the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated. Next, the polymerization slurry was continuously sent to a centrifuge so that the level of the polymerization reactor was kept constant, and the polymer was separated from the other components such as the solvent, etc. At that time, the content of the solvent, etc. relative to the polymer was 45% by mass. The separated high density polyethylene powder was dried at 85° C. with nitrogen blowing to obtain a powdered high density polyethylene (A-9).

[0096] The physical properties of the resulting high density polyethylene (A) are shown in Table 1 below.

[0097] [Table 1]

[0098] (Low density polyethylene (B)) <Production of low density polyethylene (B-1)> Using ethylene gas as a raw material, a polymer was polymerized in an autoclave reactor at a polymerization temperature of 255° C., a polymerization pressure of 130.0 MPa, and using t-butyl peroxyacetate as a polymerization initiator. Next, unreacted ethylene gas was separated in a gas separation apparatus adjusted to 50.0 MPa and 240° C. Furthermore, unreacted gas was separated in a gas separation apparatus adjusted to 2.0 MPa and 240° C. The residence time of the polymer in each gas separation apparatus was 15 minutes. The molten polymer was then granulated using a single-screw extruder manufactured by Nippon Steel Corporation (screw diameter 100 mm, L / D = 24, L: distance from raw material supply inlet to discharge outlet (m), D: inner diameter of extruder (m). The same applies below.) to obtain pelletized low-density polyethylene (B-1). The resulting low-density polyethylene (B-1) had a density of 919 kg / m 3 The MFR was 4.0 g / 10 min.

[0099] <Production of low density polyethylene (B-2)> A low-density polyethylene (B-2) was obtained by carrying out polymerization in the same manner as in the production of the low-density polyethylene (B-1), except that the polymerization temperature was 230° C., the polymerization pressure was 150.0 MPa, and 1.2 mol % of the ethylene raw material was changed to propylene. The resulting low-density polyethylene (B-2) had a density of 922 kg / m 3 The MFR was 5.0 g / 10 min.

[0100] <Production of low density polyethylene (B-3)> Using ethylene gas as a raw material, a polymer was polymerized in a tubular reactor at a polymerization temperature of 270°C, a polymerization pressure of 230 MPa, and using t-butylperoxy-2-ethylhexanoate as a polymerization initiator. Next, unreacted ethylene gas was separated in a gas separation apparatus adjusted to 70.0 MPa and 230° C. Furthermore, unreacted gas was separated in a gas separation apparatus adjusted to 2.0 MPa and 230° C. The residence time of the polymer in each gas separation apparatus was 20 minutes. The molten polymer was then pelletized using a single-screw extruder (screw diameter 100 mm, L / D=24) manufactured by Japan Steel Works, Ltd., to obtain pelletized low-density polyethylene (B-3). The resulting low-density polyethylene (B-3) had a density of 916 kg / m3 The MFR was 4.0 g / 10 min.

[0101] <Production of low density polyethylene (B-4)> Polymerization was carried out in the same manner as in the production of the low-density polyethylene (B-1), except that the polymerization temperature was 220° C., the polymerization pressure was 120.0 MPa, and 18.5 mol % of the ethylene raw material was changed to butane, to obtain a low-density polyethylene (B-4). The resulting low-density polyethylene (B-4) had a density of 924 kg / m 3 The MFR was 6.0 g / 10 min.

[0102] <Production of low density polyethylene (B-5)> Polymerization was carried out in the same manner as in the production of the low-density polyethylene (B-1), except that the temperature of the gas separator was set to 200° C., to obtain a low-density polyethylene (B-5). The resulting low-density polyethylene (B-5) had a density of 919 kg / m 3 The MFR was 4.0 g / 10 min.

[0103] <Production of low density polyethylene (B-6)> Polymerization was carried out in the same manner as for the low-density polyethylene (B-1), except that the polymerization temperature was 255°C, the polymerization pressure was 130.0 MPa, 18.5 mol% of the ethylene raw material was changed to butane, the gas separator temperature was set to 265°C, and the residence time was set to 35 minutes, to obtain a low-density polyethylene (B-6). The resulting low-density polyethylene (B-6) had a density of 925 kg / m 3 The MFR was 8.0 g / 10 min.

[0104] <Production of low density polyethylene (B-7)> Polymerization was carried out in the same manner as for the low-density polyethylene (B-3), except that the polymerization temperature was 250°C, the polymerization pressure was 200.0 MPa, 18.5 mol% of the ethylene raw material was changed to butane, the gas separator temperature was set to 200°C, and the polymer residence time in the gas separator was set to 15 minutes, to obtain a low-density polyethylene (B-7). The resulting low-density polyethylene (B-7) had a density of 924 kg / m 3 The MFR was 1.0 g / 10 min.

[0105] <Production of low density polyethylene (B-8)> With reference to the method of Example (B-10) of Japanese Patent No. 6,912,290, polymerization was carried out in an autoclave reactor in the same manner as for the low-density polyethylene (B-1), except that the polymerization temperature was 256°C, the polymerization pressure was 122 MPa, t-butyl peracetate and t-butyl peroctate were used as initiators in a molar ratio of 1:9 diluted with isododecane to give a concentration of 30% by mass, the gas separator temperature was set to 265°C, and the polymer residence time in the gas separator was set to 35 minutes. Thus, a low-density polyethylene (B-8) was obtained. The resulting low-density polyethylene (B-8) had a density of 918 kg / m 3 The MFR was 7.0 g / 10 min.

[0106] The physical properties of the obtained low-density polyethylene (B) are shown in Table 2 below.

[0107] [Table 2]

[0108] (Polyethylene composition) Example 1: Production of Polyethylene Composition C-1 To powdered high-density polyethylene (A-1), pellet-form low-density polyethylene (B-1) was added using a side feeder so that the mixture was 90% by mass of (A-1) and 10% by mass of (B-1). The mixture was melt-kneaded at a set temperature of 200°C using a twin-screw extruder (screw diameter 44 mm, L / D = 35) manufactured by Nippon Steel Corporation, and then melt-kneaded at a set temperature of 200°C using a single-screw extruder (screw diameter 100 mm, L / D = 24) manufactured by Nippon Steel Corporation, and granulated into pellets.

[0109] <Example 2> Preparation of polyethylene composition C-2 Powdered high density polyethylene (A-1) was melt-kneaded at a set temperature of 200°C using a twin screw extruder (screw diameter 44 mm, L / D = 35) manufactured by Nippon Steel Corporation, and granulated into pellets. The obtained pelleted high density polyethylene (A-1) and pelleted low density polyethylene (B-1) were mixed at 85% by mass and 15% by mass, respectively, and mixed for 2 hours using a tumbler type blender. The blended mixture was melt-kneaded at a set temperature of 200°C using a single screw extruder (screw diameter 100 mm, L / D = 24) manufactured by Nippon Steel Corporation, and granulated into pellets.

[0110] <Example 3: Production of Polyethylene Composition C-3> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-2) and the high-pressure low-density polyethylene resin (B-3) were used in amounts of 80 mass% and 20 mass%, respectively.

[0111] <Example 4 Production of Polyethylene Composition C-4> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-2) and the high-pressure low-density polyethylene resin (B-2) were used in amounts of 90% by mass and 10% by mass, respectively.

[0112] <Example 5 Production of Polyethylene Composition C-5> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-3) and the high-pressure low-density polyethylene resin (B-1) were used in amounts of 70% by mass and 30% by mass, respectively.

[0113] <Example 6 Production of Polyethylene Composition C-6> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-4) and the high-pressure low-density polyethylene resin (B-4) were used in amounts of 80 mass% and 20 mass%, respectively.

[0114] <Example 7 Production of Polyethylene Composition C-7> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-5) and the high-pressure low-density polyethylene resin (B-1) were used in amounts of 95% by mass and 5% by mass, respectively.

[0115] <Example 8 Production of Polyethylene Composition C-8> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-1) and the high-pressure low-density polyethylene resin (B-5) were used in amounts of 80 mass% and 20 mass%, respectively.

[0116] <Example 9> Preparation of Polyethylene Composition C-9 The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-6) and the high-pressure low-density polyethylene resin (B-3) were used in amounts of 85% by mass and 15% by mass, respectively.

[0117] <Example 10: Production of Polyethylene Composition C-10> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-3) and the high-pressure low-density polyethylene resin (B-6) were used in amounts of 90% by mass and 10% by mass, respectively.

[0118] < Reference example 11. Production of polyethylene composition C-11 The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-1) and the high-pressure low-density polyethylene resin (B-1) were used in amounts of 65% by mass and 35% by mass, respectively.

[0119] <Comparative Example 1: Production of Polyethylene Composition C-12> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-1) and the high-pressure low-density polyethylene resin (B-1) were used in amounts of 40% by mass and 60% by mass, respectively.

[0120] <Comparative Example 2: Production of Polyethylene Composition C-13> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-5) and the high-pressure low-density polyethylene resin (B-5) were used in amounts of 90% by mass and 10% by mass, respectively.

[0121] <Comparative Example 3: Production of Polyethylene Composition C-14> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-2) and the high-pressure low-density polyethylene resin (B-8) were used in amounts of 65% by mass and 35% by mass, respectively.

[0122] <Comparative Example 4: Production of Polyethylene Composition C-15> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-6) and the high-pressure low-density polyethylene resin (B-6) were used in amounts of 85% by mass and 15% by mass, respectively.

[0123] <Comparative Example 5: Production of Polyethylene Composition C-16> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-7) and the high-pressure low-density polyethylene resin (B-1) were used in amounts of 80 mass% and 20 mass%, respectively.

[0124] <Comparative Example 6: Production of Polyethylene Composition C-17> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-8) and the high-pressure low-density polyethylene resin (B-3) were used in amounts of 90% by mass and 10% by mass, respectively.

[0125] <Comparative Example 7: Production of Polyethylene Composition C-18> The polyethylene composition (C-1) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-1), except that the high-density polyethylene resin (A-9) and the high-pressure low-density polyethylene resin (B-1) were used in amounts of 85% by mass and 15% by mass, respectively.

[0126] <Comparative Example 8: Production of Polyethylene Composition C-19> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-1) and the high-pressure low-density polyethylene resin (B-7) were used in amounts of 80 mass% and 20 mass%, respectively.

[0127] <Comparative Example 9: Production of Polyethylene Composition C-20> The polyethylene composition (C-2) was melt-kneaded and pelletized in the same manner as in the polyethylene composition (C-2), except that the high-density polyethylene resin (A-9) and the high-pressure low-density polyethylene resin (B-8) were used in amounts of 80 mass% and 20 mass%, respectively.

[0128] The physical properties and evaluation results of the obtained polyethylene compositions are shown in Tables 3 and 4 below.

[0129] [Table 3]

[0130] [Table 4] [Industrial Applicability]

[0131] INDUSTRIAL APPLICABILITY The polyethylene composition of the present invention has industrial applicability particularly as a raw material for film applications in which fisheye quality and heat resistance are important, such as surface protective films and the like.

Claims

1. A polyethylene composition comprising a high-density polyethylene (A) having a density of 942 kg / m3 or more and a high-pressure low-density polyethylene (B) having a density of 930 kg / m3 or less, and which satisfies the following <Condition (A)> to <Condition (D)> and <Condition (F)>. <Condition (A)> Weight average molecular weight measured by gel permeation chromatography (GPC) is 4 It is equal to or greater than 0,000 g / mol and equal to or less than 350,000 g / mol. <Condition (B)> The degree of crystallinity calculated by wide-angle X-ray scattering (WAXS) measurement is 60% or more and 75% or less. do. <Condition (C)> The crystallite size of the (110) plane calculated by the wide-angle X-ray scattering measurement is 17 nm or more. It is less than 2 nm. <Condition (D)> In the temperature variable wide-angle X-ray scattering measurement, the peak intensity X originating from the (110) plane at 50 °C and the peak intensity X originating from the (110) plane at 1 Ratio of peak intensity Y originating from the (110) plane at 30° C.: Y / X is 0.40 or more and 0.80 or less The following is the result. <Condition (F)> Cross fractionation chromatography (CFC) temperature rising elution fractionation (TREF) up to 80°C The mass ratio of the eluted components is 1 mass % or more and 35 mass % or less of the total eluted amount.

2. Pulsed NMR measurement at 180°C, Carr Purcell Meiboom When the free induction decay curve obtained by the Gill (CPMG) method was approximated with three components, the low-mobility component The relaxation time Tα of the low motility component α is 5 ms or more and 25 ms or less, and the proportion of the low motility component α is The total Rα is 25% or more and 55% or less. The polyethylene composition of claim 1.

3. The polyethylene composition comprises: Density is 942 kg / m 3 and a high density polyethylene (A) having a density of 930 kg / m 3 A mixture of high-pressure low-density polyethylene (B) as follows: When the high-pressure low-density polyethylene (B) is subjected to pulse NMR measurement at 180° C., a free induction decay curve obtained by a Carr Purcell Meiboom Gill (CPMG) method is approximated with three components, and the low mobility component ratio calculated by the following (Formula I) from the abundance ratio Rα of the low mobility component α and the abundance ratio Rβ of the intermediate component β is 0.35 or more and 0.55 or less. The polyethylene composition of claim 1. (Ratio of low mobility component)=Rα / (Rα+Rβ) (Equation I)

4. The polyethylene composition comprises: Density is 942 kg / m 3 and a high density polyethylene (A) having a density of 930 kg / m 3 A mixture of high-pressure low-density polyethylene (B) as follows: When the high-density polyethylene (A) is subjected to a pulse NMR measurement at 180° C., a three-component approximation of a free induction decay curve obtained by the Carr Purcell Meiboom Gill (CPMG) method is performed, and the low mobility component ratio calculated by the following (Formula I) from the abundance ratio Rα of the low mobility component α and the abundance ratio Rβ of the intermediate component β is 0.50 or more and 0.70 or less. The polyethylene composition of claim 1. (Ratio of low mobility component)=Rα / (Rα+Rβ) (Equation I)

5. The content of the high-density polyethylene (A) is 70% by mass or more and 99% by mass or less, The content of the high-pressure low-density polyethylene (B) is 1% by mass or more and 30% by mass or less. The polyethylene composition according to claim 3 or 4.

6. A molded article comprising the polyethylene composition according to claim 5.

7. The molded article according to claim 6, which is a film.

Citation Information

Patent Citations

  • Resin composition

    JP1988003043A

  • Polyethylene based resin composition

    JP1991237144A

  • Polyethylene resin composition

    JP1992041537A

  • Ethylene-based polymer composition

    JP1996302083A

  • Blow-molded body

    JP1999138618A